Assessment of Lean Initiatives : An Investigation in the Indian Apparel Export Industry - Kaur, Prabhjot; Marriya, Kavita; Kashyap, Radha (Prabandhan: Indian Journal of Management, 2016)
Lean is a philosophy of continuous development, and making the evaluation of its effects on a business against the expected value-adds further assists the business managers to make strategic decisions on the adoption of new productivity improvement initiatives. The present study was designed to comparatively assess the status of the lean initiatives among lean initiated and non-lean initiated apparel units. The study was limited to 10 selected lean initiated and non - lean initiated apparel units, each manufacturing ladies garments in the National Capital Region (India) using inclusion and exclusion criteria from the member list of Apparel Export Promotion Council, Gurgaon, India. The status was evaluated on the basis of seven lean bundles formed by combining 33 lean enterprise practices and using six- stage assessment matrix from the traditional to world class on the basis of the total scores obtained. The result revealed that most of the lean initiated apparel units were at the planning, learning, initiation, and improving stage that is phase I or II, while only one unit was found to be at phase III, that is, at extensive lean introduction and results visibility phase and had a long way to go towards complete transformation. Still, a significant difference was found in the current status of lean initiatives among lean initiated and non-lean initiated apparel units. The lean assessment matrix developed can also be used by other apparel manufacturing units actively engaged in their lean journey to benchmark themselves against the â€œbest in classâ€ lean standard.